End-of-life management of corrosive drywall. (1st November 2016) - Kim, Hwidong; Krause, Max J.; Townsend, Timothy
Abstract: Recently, gypsum drywall products imported to the United States (US) were found to cause metal corrosion and tarnishing in some homes, often necessitating that this drywall be discarded. Research assessed the potential implications of recycling and landfilling corrosive/imported drywall. Samples of corrosive drywall were collected from homes in Florida, US and these characteristics were assessed relative to domestically-produced drywall purchased from retail outlets. The total and synthetic precipitation leaching procedure (SPLP) leachable heavy metal concentrations were measured and compared to risk-based regulatory thresholds to assess the possible land application risk. In a majority of samples, concentrations were below levels of regulatory concern. The mean concentration of several elements exceeded the thresholds in a few samples for the direct exposure assessment (As) and the groundwater leaching assessment (Al, B, Hg, Mn, Sr and V); but the results did not suggest that corrosive drywall would present a greater risk than domestic drywall. To assess landfilling concerns, the potential for sulfur gases emissions upon disposal was evaluated. Experiments indicated that corrosive drywall would not pose a greater risk of long-term H2 S emissions compared to domestic drywall. Graphical abstract: Highlights: US-domestic and imported corrosive drywall products were evaluated for potential disposal risks. Corrosive and domestic drywalls can be managed as non-hazardous wastes. Corrosive drywall did not pose a greater risk of long-term H2 S emissions in simulated C&D landfills. Corrosive drywall can be managed in a similar manner as discarded domestic drywall.